The Effect of Time on Root Coverage Outcomes: A Network Meta-analysis. (October 2019) - Tavelli, L.; Barootchi, S.; Cairo, F.; Rasperini, G.; Shedden, K.; Wang, H.L.
The stability of root coverage outcomes has gained a great deal of interest. However, insufficient evidence is available, mainly due to limited direct comparisons among different techniques and the small sample size among clinical trials. Therefore, the aim of this study was to propose a mixed-models network meta-analysis (NMA) that includes the novelty of assessing time on root coverage outcomes while simultaneously comparing different surgical approaches. A literature search was performed by 2 individual reviewers to identify randomized clinical trials (RCTs) reporting the outcomes of root coverage procedures of at least 2 time points to estimate the slopes of different treatment approaches. The primary outcomes were the changes in slopes for recession depth (REC), keratinized tissue width (KTW), and clinical attachment level. Sixty RCTs with a total of 2, 554 gingival recessions (1, 864 patients) were included in the NMA. Connective tissue graft (CTG) and enamel matrix derivative (EMD) approaches provided superior initial REC reduction compared to flap advancement alone. However, only CTG-based procedures were effective in maintaining the stability of the gingival margin over time, while EMD, acellular dermal matrix, collagen matrix, and flap alone showed a similar tendency for gingival recession recurrence. Baseline REC and KTW at the earliest postoperative recall were predictors for the stability of the gingival margin. In addition, a geographic center effect on the treatment slopes was observed for REC and KTW. While limitations of the present linear mixed-modeling approach should be considered as it refers to estimation and comparison of time slopes based on an examined while linear framework, the designed NMA showed to be an effective tool for the simultaneous comparison of multiple treatment approaches while taking into account the critical element of time.